Assessment of the State of Implementation of Excellence Model Common Assessment Framework (CAF) 2013 by the National Institutes of Research – Development – Innovation in Romania - Cristina Raluca Popescu; Gheorghe N. Popescu; Veronica Adriana Popescu (Amfiteatru Economic)
The paper highlights the part of the results of a research based on a questionnaire conducted at the National Institutes for Research, Development and Innovation (NIRDI) of Romania, under the coordination, under the authority or the subordination of the National Agency for Scientific Research and Innovation (NASRI), goals being pursued: Assess the current status of implementation of the Common model of excellence Self-Assessment framework (CAF) in 2013 by NIRDI in Romania; Determining the impact that the implementation of one or more management systems has on achieving excellence in research and innovation; Capacity assessment CAF 2013 model of excellence to provide enlightening information on the most important risks and challenges facing the entity being (self-) evaluation. The research was conducted in July 2016 to a representative sample of 51 of the 53 INCDI, under the coordination, under the authority or subordinate NASRI. It appears that although there is a high degree of fulfillment of the 9 criteria of the excellence model CAF 2013 NIRDI have not assimilated the spirit and the purpose of the excellence model induced by the principles of total quality management by importance (percentage) given to each criterion and sub-criterion. It appears real progress criteria "results on customers" and "processes, products and services". At the same time there are serious shortcomings in the criteria "results on the organization" and "results on the staff." On the one hand, based on the results analyzed, it was determined that to achieve excellence in research is not sufficient to implement two or more management systems, on the other hand it was confirmed that the results of (self-) evaluation stage of implementation of the model of excellence CAF 2013 provides significant and enlightening information to identify the principal risks and deficiencies faced by the entity (self) assessed.